Community Engaged Lifestyle Modification Research: Engaging Diabetic and Prediabetic African American Women in Community-Based Interventions - Starla Hairston Blanks; Henrie Treadwell; Anya Bazzell; Whitney Graves; Olivia Osaji; Juanita Dean; James T. McLawhorn; Jareese Lee Stroud (Hindawi Limited, 2016)
Purpose. The I Am Woman (IAW) Program is a community-based, culturally responsive, and gender-specific nutrition, obesity, and diabetes educational prevention program designed for African American women (AAW). Chronic nutrition-related health conditions such as excess body weight, diabetes mellitus, cardiovascular disease, and some forms of cancer are common among many African American women. Methods. IAW engaged AAW at risk for such deleterious health conditions by developing a health education intervention that aimed to support weight loss and management, improve knowledge about healthy lifestyle behavioral choices, and facilitate increased access to comprehensive healthcare. This Community Health Worker- (CHW-) led program enrolled 79 AAW aged 18 and older in a 7-week group health education intervention. Results. Following the intervention, results indicated that participants had greater knowledge about nutrition and health, strategies for prevention and management of obesity and diabetes, increased engagement in exercise and fitness activities, and decreased blood pressure, weight, body, and mass index. Cholesterol levels remained relatively unchanged. Additionally, AAW visited a primary care doctor more frequently and indicated greater interest in addressing their health concerns. Conclusion. This model of prevention appears to be a promising approach for increasing awareness about ways to improve the health and well-being of AAW.